2022
DOI: 10.3390/foods11071050
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Glucose Response after Consuming Low-Carbohydrate, Low-Calorie Rice Cooked in a Carbohydrate-Reducing Rice Cooker

Abstract: This study evaluates whether blood glucose response differs upon consuming rice cooked in a carbohydrate (carb)-reducing rice cooker. Rice cooked this way exhibited 19% reduced total carbohydrate (34.0 ± 0.3 vs. 27.6 ± 0.9 g/100 g rice) and 20% reduced total calorie (149.0 ± 1.0 vs. 120.8 ± 3.7 kcal/100 g rice) contents. We measured the blood glucose response (at 0, 15, 30, 45, 60, 90, and 120 min) in 13 healthy participants after consuming 6 different rice types: regular white rice (regular WR, 50 g of availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…It was reported that rice cooked using carb‐reducing rice cookers exhibited 19% reduced total carbohydrate, contributing to the reduction of early postprandial spikes in blood glucose level of healthy subjects. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that rice cooked using carb‐reducing rice cookers exhibited 19% reduced total carbohydrate, contributing to the reduction of early postprandial spikes in blood glucose level of healthy subjects. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…Foods with levels of high fibre are typically low in calories as well as low in sugar and fat, which can help reduce the occurrence of obesity and heart disease [ 41 ]. According to Ahn et al [ 42 ], fibre increases the density and thickness of food in the digestive tract and inhibits the movement of enzymes, slowing the digestive process and lowering the sugar response in people with DM. Dietary fibre also aids in the digestive process, slows glucose absorption, lowers the levels of cholesterol and low-density lipoprotein (LDL) and stimulates the production of short-chain fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, fibre consumption has a beneficial effect on blood glucose levels in people with diabetes [ 47 ]. Ahn et al [ 42 ] proposed that fibre reduces the activity of digestive enzymes and the level of food penetration, supported by their finding that consumption of rice analogues with a fibre content of up to 22.1% significantly lowered blood sugar levels in diabetic rats (Δ 175 mg/dL). Furthermore, the addition of VCO to corn cookies has been shown to aid in the reduction in blood sugar levels in mice, while, similarly, [ 48 ] stated that the feeding of VCO lowered blood sugar levels in rats.…”
Section: Resultsmentioning
confidence: 99%